Designing an intelligent system for personalized development of graphomotor skills in preschool children based on analysis of deviations from the standard - Aitymova, Aliya; Shaporeva, Anna; Kopnova, Oxana; Petrova, Anastasia; Karymsakova, Anara; Abildinova, Gulmira; Iklassova, Kainizhamal; Aitymov, Zhanat (Eastern-European Journal of Enterprise Technologies, 2025)
This study’s object is the process that forms and develops graphomotor skills in preschool children by using digital educational technologies. Graphomotor skills, which are a subset of fine motor skills, are critical for the development of writing and academic success, especially in the early stages of schooling. The problem relates to the lack of individualization, objective diagnostics, and adaptive correction in conventional methods. When teaching using traditional methodology, handwriting analysis is often subjective while the process of skill formation is complex and requires the integration of cognitive, motor, and motivational factors. The electronic application "Dexterous Fingers" uses mathematical modeling, in particular piecewise linear approximation followed by smoothing with Catmull-Rom splines, for automatic and objective analysis of writing trajectories in real time. This makes it possible not only to quantitatively and qualitatively assess deviations from reference samples but also generate personalized recommendations and tasks. The electronic application maintains a high level of motivation and involvement of children due to interactive and game elements, and ensures the availability of specialized assistance, especially in resource-limited settings. The application includes an effective monitoring and reporting system, providing parents and teachers with detailed data on the child’s progress. The results after the implementation of the application demonstrate a pronounced positive trend in children in the experimental group. The proportion of children with a high level of graphomotor skills increased to 46%, while the number of children with a low level decreased to 21%